2006
DOI: 10.1177/0193945905282305
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization History and Differences in Self-Rated Pregnancy Risk

Abstract: High-risk pregnancies affect a significant number of women each year. Limited information exists on how these women appraise the risk to their pregnancy. This descriptive study of expectant women who were medically categorized as high risk examined differences in women's self-appraisal of risk to themselves and their babies, based on hospitalization history, and differences among risk appraisals made by women and their health care providers. Women who were currently hospitalized had significantly lower self-ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 21 publications
1
41
0
1
Order By: Relevance
“…Several studies have reported a distinction between women's perceptions of risk to the baby, and risk to themselves or the pregnancy (Gray, 2006;Gupton et al, 2001;Maloni & Kutil, 2000) -illustrating the complexity of the concept. While the current study also distinguished between perceived risk to mother and perceived risk to baby, these were assessed using only four single-item measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported a distinction between women's perceptions of risk to the baby, and risk to themselves or the pregnancy (Gray, 2006;Gupton et al, 2001;Maloni & Kutil, 2000) -illustrating the complexity of the concept. While the current study also distinguished between perceived risk to mother and perceived risk to baby, these were assessed using only four single-item measures.…”
Section: Discussionmentioning
confidence: 99%
“…Yet it is essential to develop valid and reliable tools, which are sensitive to change. Other researchers have utilised visual analogue scales (Gray, 2006;Gupton et al, 2001) and acknowledged the need for refinement and psychometric testing of these scales. Exploration of the factors contributing to perceptions of risk, the processes by which women construct these meanings, and the potential for differing internal working models of attachment among women would benefit from detailed qualitative investigation.…”
Section: Discussionmentioning
confidence: 99%
“…These included six cross-sectional studies of women with high risk pregnancies (Heaman, Beaton et al 1992;Gupton, Heaman et al 2001;Gray 2006;White, McCorry et al 2008;Headley and Harrigan 2009;Heaman and Gupton 2009) and one retrospective study of mothers of twins conducted within the first three days following delivery (Papiernik, Tafforeau et al 1997).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…All measures were developed by study authors. Within the cross-sectional studies, Heaman et al (1992), Gray (2006) and White et al (2008) used their own measures. Gupton et al (2001) developed and used the Perception of Pregnancy Risk…”
Section: Measurement and Data Analysismentioning
confidence: 99%
“…Exactly how they feel about the pregnancy will be affected by how they perceive the level of risk. Studies of risk perception show an individual's perception of risk is a subjective response based on previous life experiences, coping strategies, the context in which the risk occurs, the degree of perceived control, and the weight attached to information about the risk obtained from a variety of sources (Alaszewski and Horlick-Jones 2003;Edwards et al 2002;Gray 2006). This is also true of risk perception in pregnancy (Jordan and Murphy 2009;White et al 2008).…”
Section: Introductionmentioning
confidence: 99%